How Does the Accounting Treatment of the Environment Transaction and How it Impacts to Company's Performance? Case from Indonesia - Einde Evana; Lindrianasari Lindrianasari; R. Weddie Andriyanto (Universitas Pasundan, 2019)
This study aims to investigate the awareness of big companies in Indonesia on the allocation of environmental costs. This research is very important to do, given that the company's operational effects as contributing very large carbon emissions (especially companies whose activities are in contact with nature). The method used in this research is observation, by tracing the existence of environmental cost in every big company in Indonesia, which is in database Bloomberg. The number of samples of this study is 2,043, for all companies in the period of observation 2004–2017. The results of this study indicate a relatively slow response of companies in responding to regulations issued by the state. This also indicates the low compliance of large companies in Indonesia for the implementation of the rules, in terms of accounting known as the recognition and measurement of accounting for environmental transactions.